Correction For Pid Controller Value For Bus Suspension Model With Matlab - A.M Shiddiq Yunus (Politeknik Negeri Ujung Pandang, 2008)
One important thing of design the real system is to make a simulation to find out the optimal and the best performance of the system. Bus suspension has been modeling for some control and simulation systems and this paper is aimed to find the better performance of bus suspension system with PID Controller. The main idea of this paper is to discuss about the correction for better result in controlling the bus suspension system using PID Controller through Simulink in Matlab program. The result shows that in this design, the PID controller zeroes are located at -4 and -27 on the real axis. The desired pole locations have been determined and are located at -362, -31, -1 -2-j12.3 and -2+j12.3. For the value of PID, it desired to put the gains for Ki, Kp, and Kd respectively: 11153000, 3065000, and 100261. From the plotted graphic, it can be seen that there is an approximate overshoot of 12% and a settling time of around 1 second.